Hidrodinâmica das zonas cárstica e cárstica-fissural do sistema aquífero da Formação Sete Lagoas por meio de traçadores corantes e da análise das estruturas rúpteis na região de Lagoa Santa, Minas Gerais - Maria Isabel Pereira Teodoro (2020)
The studied area is located 30 km north of Belo Horizonte and includes within its limits the Environmental Protection Area Carste of Lagoa Santa. The Sete Lagoas Formation is the main outcrop unit, configuring a diverse karst geomorphology, characterized by canyons, blind valleys, dolines, sinkholes and caves. On the subsurface, a pipe network forms karst aquifers that shelter important water reserves, which have been suffering qualitative and quantitative risks due to the intense pressure of the demographic and industrial expansion of the region. Employing the dye tracer injection technique, it has been an attempt to establish the hydraulic interconnections, the hydrodynamic conditions of the flow path and the recharge, circulation and discharge configurations in the upper portion of the aquifer. Ten qualitative and quantitative assays were performed using Fluorescein and Rhodamine WT. Positive results for water interconnections were observed in seven tests, revealing the origin of 68.3%, 13.0%, 70.2%, 41.3% of the discharge in the main springs of the area: Gordura, Samambaia, Engenho and Mocambo, respectively. The apparent average flow velocity of the water in the evaluated routes ranged from 8.90x10-3 m/s to 4.49x10-2 m/s, and, considering the sinuosity factor of the route, from 1.34x10-2 m/s to 6.74x10-2 m/s, which shows the high velocity of the flows. Considering the direct interconnections, where more than 85% of the injected dye mass was recovered, there is a spatial zoning of the velocities, in such form so that the highest values occur in the northern region of the area - contributions from Gordura spring, the intermediate values occur in the southern region - contributions from Samambaia stream and the lowest velocities in the central portion - contributions from Mocambo spring. From the measurement of the flow rates at the injection and monitoring points, the mean residence time and the percentage of tracer mass recovered, the aquifer volumes for the investigated routes were calculated, which ranged from 1512.81 m³ to 38,246.4 m³ and the diameters of the conduits, which ranged from 0.63 m to 2.40 m. The interconnections present mostly directions of flow to the east sector, mainly in the directions N40°-60°E and N80°-90°E, towards the regional base level, the Rio das Velhas river. The evaluation of the flow in the wells associated with morphostructural lineaments also evidenced the importance of these same directions in the conditioning of the underground water circulation, so that the largest flows of the deep wells are related to the N67,5°-90°E directions (median of 52 .59 m³/h and average of 98.16 m³/h), N270°-292,5°W (median of 23.23 m³/h and average of 38.71m³/h) and N22,5°-45°E (median of 15.6m³/h and average of 52.76m³ / h). The preferred flow directions obtained for both the upper and lower portions of the aquifer are well marked by the morphostructural lineaments, fractures, bedding and paleoducts, which show the strong structural control in the conditioning of the underground flow in the region.